Time perspective and significance of life events in adolescence - N. P. Shilova; A. K. Vladyko (Вестник университета)
This article presents the results of a study of the relationship between the time perspective and themes of significant life events in adolescence. The study involved 1,394 boys and girls aged 14 to 23 years. It was revealed that there is an age-related multidirectional dynamics in the representation of the following periods: “studying at school”, “vocational training”, “professional autonomy”, “future”, “open present”. For example, modern youth associate “learning at school” positively with entertainment and negatively with study and work in the past and with communication and contacts in the future. The period of “professional training” is associated with all significant events in their lives except for events related to entertainment in the future. The period of “professional autonomy” is associated with events aimed at business (including both professional activity and study) both in the past and in the future. All important events in the present depend on the desire to possess some qualities, properties, skills. And at the same time, the significance of communication and entertainment in the past and the importance of entertainment and specific activities (educational and professional) in the future are associated with this desire. The results of the study may be of interest for the organization of work with high school students and students on the formation of a time perspective of the future.